MAPPING OF AQUATIC INVASIVE ANIMALS IN CA MAU PROVINCE - Nam, Le Hoai; Duc, Pham Anh (GeoScience Engineering, 2018)
This study to enhance the discussion about the usefulness of invasive animals for biodiversity assessment in Mekong Delta provinces. Data have used the area of 5.331 km² Ca Mau Province [1]. The data covered the period 2017 – 2018. To implement this evaluation, the analyses were based on the scientific documents “Introduction to Invasive Species in Vietnam” of Vietnam Agency of Biodiversity Conservation and “The Aquatic Invasive Species Assessment and Management Plan” Massachusetts Department of Conservation and Recreation, and the working experiences of research group for the invasive species assessment [2, 3]. The results found two invasive animal species such as apple snail – Pomacea canaliculata (Lamarck, 1819) and Amazon sailfin catfish – Pterygoplichthys pardalis (Castelnau, 1855) [2]. These species mapped in the map of Ca Mau Province. The problem of invasive species has become an important issue of concern for the local government and community. However, if appropriate targets for ecosystem management planning is suggested, these "invaders" can be prevented the spread of invasive species. Keywords: aquatic invasive species, biodiversity assessment, Mekong Delta https://doi.org/10.2478/gse-2018-0009